RAPD positive: Which eye is abnormal? - Shalihin, Mohd Shaiful Ehsan (Malaysia Medical Gazette, 2015)
Relative afferent pupillary defect (RAPD) test is a common screening tool used by medical personnel in the ophthalmology clinic when seeing newly referred cases. It is done routinely prior to consultation with a medical officer. Even medical students are reminded to perform the RAPD test as part of a complete cranial nerve examination. Despite its wide application, many still do not understand the real function of the RAPD test and wrongly interpret its results. Is it possible to identify the normal or abnormal eye based on the result of the RAPD test? To correctly answer this question, we need to have a closer look at how our eyes work. The pupils constrict in response to light and dilate in absence of light, a phenomenon known as the pupillary light reflex. The beauty of this is that both pupils will constrict even if only one eye is stimulated by a light source. This is called the consensual light reflex. It requires an intricate coordination between various components of the visual pathway; the optic nerve transmits impulses from retinal photoreceptors to the midbrain, impulses that then travel to the ciliary ganglia via the oculomotor nerve and cause equal constriction of both pupils